Pola Kredit Usaha Mikro Kecil Menengah (UMKM) Kelompok Bank dan Fintech di Indonesia - Dipa Teruna; Tedy Ardiansyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Abstract: The purpose of this study is to find models or patterns from bank and fintech groups for the progress of MSMEs (micro, small and medium enterprises) in assisting with funding and supervision related to finance. The research method is a qualitative research where the approach is carried out through a literature study, namely research that examines critically knowledge, ideas or findings and provides theoretical and methodological contributions to the object of study. The data used are secondary data in the form of interviews. The results of this study show that the map or model of each bank and fintech has formed policies that support each other, both banks and fintech. Banks must support MSMEs with appropriate and effective PKB (Bank Credit Distribution) policies for MSME actors or entrepreneurs and KB (Bank Policy) which must be flexible, friendly and controlled to MSME actors or entrepreneurs so that they do not experience total losses or go bankrupt. While Fintech has similarities in determining policies by informants, namely KF (Fintech Policies) and TF (Fintech challenges) where these 2 policies will trigger the success of MSME actors or entrepreneurs in carrying out entrepreneurial activities with fintech support. Keywords:UMKM, Credit, Bank, Fintech